STRATEGI PEMBELAJARAN INOVATIF MAKE A MATCH PADA MATERI BUKTI BERIMAN: MEMENUHI JANJI, MENSYUKURI NIKMAT, MEMELIHARA LISAN, DAN MENUTUP AIB ORANG LAIN - Nurul Maghfiroh; Anita Puji Astutik (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
Amidst the current of globalization and accelerated technological development, Islamic religious education is faced with various challenges that demand strategic and adaptive responses. Therefore, innovation in learning strategies is needed to make the educational process more interactive and relevant. This study aims to evaluate the implementation of an innovative learning approach known as Make a Match and to determine the advantages and challenges of this approach. This study applies a descriptive qualitative method which was carried out at SMK Negeri 3 Buduran with research subjects including PAI teachers, students, and curriculum representatives. The research results prove that the Make a Match learning model can make lessons more interesting. This strategy successfully increases accuracy, speed of thinking, enthusiasm for learning, and positive cooperation and social interaction skills. Studies show that the Make a Match learning model can make Islamic Education learning more active, fun, and meaningful if used with good learning planning and proper classroom management.